A succinct strategy for construction of nanoporous ionic organic networks from a pyrylium intermediate. Issue 89 (24th October 2019) - Che, Siying; Yang, Zhenzhen; Popovs, Ilja; Luo, Huimin; Luo, Yali; Guo, Wei; Chen, Hao; Wang, Tao; Jie, Kecheng; Wang, Congmin; Dai, Sheng
Abstract : A two-step strategy under metal- and template-free conditions is presented for the fabrication of hydroxyl group and pyridinium salt-bifunctionalized nanoporous ionic organic networks with high surface area. Abstract : Hydroxyl group and pyridinium salt-bifunctionalized nanoporous ionic organic networks prepared via a simple two-step strategy under metal- and template-free conditions are presented. The structural features of the resultant polymer ( e.g. high surface area, abundant hydroxyl groups and ionic functionalities) made it a promising candidate as an efficient scavenger of toxic oxo-anions from water.